An angel for Christmas [compact disc, unabridged] - Graham, Heather (Brilliance Audio, 2011)
Christmas has never brought out the best in the MacDougal family. Still, year after year, they gather together in the Blue Ridge Mountains to try to make the season merry and bright. But this year is an especially strained one, between Shayne's impending divorce, Morwenna's slavish devotion to work, and Bobbie's reluctance to face what life has to offer. Then, in the midst of a snowy sibling shouting match, a mysterious stranger appears.